Early alterations of hippocampal gabaergic synaptic properties induced by Aβ42 oligomers: Molecular and cell biology/APP/Abeta/amyloid. (7th December 2020) - Hidisoglu, Enis; Chiantia, Giuseppe; Franchino, Claudio; Marcantoni, Andrea; Carbone, Emilio
Abstract: Background: Synaptic dysfunction is one of the earliest hallmarks of Alzheimer's Disease (AD). It is well known that the oligomeric form of amyloid β protein (Aβ42) rather than fibrils or plaques is the cause of the synaptic abnormalities and cognitive impairments associated with AD. To date, there are no comprehensive electrophysiological studies that investigate the neuronal mechanism of Aβ42‐induced synaptic changes and there is an impressive lack of information on how Aβ42 affects the elementary parameters involving GABAergic synaptic function. Method: To reveal the effects of Aβ42 on GABAergic synapses, we recorded miniature and evoked inhibitory postsynaptic currents (mIPSC and eIPSC, respectively) in c57bl6 mice embryo hippocampal neurons. mIPSC analysis and eIPSC related analysis such as paired‐pulse ratio, cumulative eIPSC amplitude and multiple probability fluctation analysis were performed to evaluate elementary parameters associated with synaptic transmission, such as unitary conductance of GABAA receptors, number of release sites, release probability, and size of readily releasable pool. Result: We found Aβ42 increased the frequency and amplitude of miniature currents as well as the amplitude of eIPSCs. When we focused on paired pulse ratio (PPR) we found that it was not changed by Aβ42, suggesting that GABA release probability was not affected by this oligomer. On the other hand, a more detailed study of the presynaptic effects induced by Aβ42 by mean of multiple probability fluctuation analysis (MPFA) and cumulative amplitude analysis has shown an increase in the size of the readily releasable pool (RRP) and number of release sites (N) without any changes of the release probability (p). Conclusion: Our results clarify the early effects induced by Aβ42 on GABAergic synapses by focusing on their pre‐ and postsynaptic site and contribute to address the development of new therapies for the treatment of AD. This project was supported by the European Molecular Biology Organization (EMBO). Project ID: EMBO‐7835.